2019
DOI: 10.14740/wjon1087
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 Gene Mutation With Helicobacter pylori Infection in Gastric Cancer Patients and Its Correlation With Clinicopathological and Environmental Factors

Abstract: Background Gastric cancer is also a leading cancer in Bangladesh like that of the global incidences. It is speculated that environmental, bacterial infection and molecular factors might have been carrying the key role of rising trend of the disease. This study was aimed to investigate the association of mutated p53 gene with of Helicobacter pylori ( H. pylori ) infection, clinicopathological and some environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The TP53 mutation rate was proved to be dependent by various parameters, including geographic characteristics known to be induced by interactions between Helicobacter pylori infection and other environmental, molecular and genetic factors[ 13 , 15 , 16 ]. In our study, which included Romanian patients, the mutation rate was 33.83%, similar to American Caucasian (40%) and Hispanic patients (43%), whereas Asian and African American patients, similar to patients in Bangladesh, proved to have significantly elevated mutations rates of 56%, 89%, and 73%, respectively[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 mutation rate was proved to be dependent by various parameters, including geographic characteristics known to be induced by interactions between Helicobacter pylori infection and other environmental, molecular and genetic factors[ 13 , 15 , 16 ]. In our study, which included Romanian patients, the mutation rate was 33.83%, similar to American Caucasian (40%) and Hispanic patients (43%), whereas Asian and African American patients, similar to patients in Bangladesh, proved to have significantly elevated mutations rates of 56%, 89%, and 73%, respectively[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lower expression of p53 was noticed in gastric epithelium of H. pylori-infected cases [29]. In the same way, a study on gastric cancer patients found that 80% of H. pylori-positive cases had p53 mutation [30]. Studies on different gastric cancer cell lines, e.g., STKM2, AGS, SNU1, and HFE145 cells, also showed that H. pylori infection resulted in p53 inhibition [31].…”
Section: Helicobacter Pylori and Gastric Adenocarcinomasmentioning
confidence: 84%
“…It has also been reported that H. pylori is able to cause mutation of P53 by inducing cytidine deaminase expression [ 40 ]. Therefore, the mutation in p53 may play a role in gastric carcinoma and may also serve as a unique biomarker and treatment target for gastric carcinoma [ 41 ].…”
Section: Reviewmentioning
confidence: 99%